2007
DOI: 10.1136/bjsm.2007.037689
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protective headgear on head injuries and concussions in adolescent football (soccer) players

Abstract: Adolescent football players experience a significant number of concussions. Being female may increase the risk of suffering a concussion and injuries on the head and face, while the use of football headgear may decrease the risk of sustaining these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 43 publications
1
80
2
1
Order By: Relevance
“…39 The authors of 1 retrospective cross-sectional study found that use of soft helmets was associated with a reduction in concussions and soft tissue injuries compared with no helmet, without increasing risk of injury to areas not covered by the head gear. 42 …”
Section: Concussionmentioning
confidence: 99%
“…39 The authors of 1 retrospective cross-sectional study found that use of soft helmets was associated with a reduction in concussions and soft tissue injuries compared with no helmet, without increasing risk of injury to areas not covered by the head gear. 42 …”
Section: Concussionmentioning
confidence: 99%
“…Football, ice hockey, lacrosse, and rugby, all report similar rates of concussion, and Delaney et al (2008) suggested that there are over 60,000 annual reported concussions in American high school sports alone. However, these numbers are vastly underrepresentative as they only reflect medically diagnosed concussions.…”
Section: Head Trauma As a Social Problem In Sportmentioning
confidence: 99%
“…123 Headgear seems to protect against soft-tissue injuries, such as lacerations, contusions, and abrasions, and is more likely to be worn by female soccer players. 123,124 Most studies have been found to have significant limitations in evaluating the potential for reducing concussions. 125 Prospective data are not currently sufficient to support recommending universal use of headgear in soccer.…”
Section: Helmets/headgearmentioning
confidence: 99%